2006
DOI: 10.1007/s11046-006-0031-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Tinea capitis in São Paulo, Brazil

Abstract: To determine the incidence of tinea capitis in São Paulo, Brazil, an investigation was performed in Private and Public Pediatrics Service involving 4,500 children from 0 to 15 years old during 5 years (1996-2000). Samples were taken from 132 children with suspected fungal infection of the scalp, for direct microscopy and culture. Tinea of scalp was mycologically confirmed in 112 patients (85%). Males were more affected than females in all age groups. Children below 8 years old accounted for more than 75% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
12

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 26 publications
0
10
0
12
Order By: Relevance
“…But in a similar study in Brazil, Moraes et al. [6] also reported isolation of T. rubrum from scalp of children, which accounted for 0.9% of the aetiologic agents they encountered.…”
Section: Discussionmentioning
confidence: 94%
“…But in a similar study in Brazil, Moraes et al. [6] also reported isolation of T. rubrum from scalp of children, which accounted for 0.9% of the aetiologic agents they encountered.…”
Section: Discussionmentioning
confidence: 94%
“…The most common isolates were M. canis (70.5%) and T. tonsurans (23.2%), followed by T. mentagrophytes (3.6%), Microsporum gypseum (1.8%) and T. rubrum (0.9%). 10 Among the fungi isolated from skin infections, the anthopophilic dermatophyte T. rubrum is the most frequent in clinical cases of tinea pedis (feet), tinea unguium (nails), tinea corporis (body) and tinea cruris (groin region). 4 Epidemiological studies conducted with university students from Sao Paulo demonstrated the occurrence of dermatophytes in 18.2% of the studied population; T. rubrum was isolated in 80% of the cases and T. mentagrophytes, in 20%.…”
Section: Epidemiological Aspectsmentioning
confidence: 99%
“…Studies performed in Brazil (8, 14, 16), Greece (9) and China (23) show that M. canis is the most prevalently isolated agent on the scalp and hair. However, in our study this agent was the second most commonly isolated, perhaps for not adapting well to the climactic conditions or because of the age group of the study population.…”
mentioning
confidence: 99%